Ordres et désordres de l’évasion carcérale - Gilles Chantraine; Tomas Martin (Criminocorpus)
Negotiated order, revolt and escape are closely linked: escapes, like revolts, justify for the institution the need to restore the image of the total institution as a place of submission and order. Far from being isolated incidents that cause chaos in a usually ordered environment, escape and revolt are an extension of the negotiated order of everyday prison life, and a revealing event of the institution's core. The reflection will be carried out in five succinct and distinct points: first, we will explore the cultural and seductive power of escape. Then we will ask what is both sociological evidence and a reality too little explored as such by sociologists: prison is and will remain, before a disciplinary institution, an anti-escape mechanism. Third, we will criticize the dominant institutional and academic knowledge of the modes of observation and classification of escape. We will then return more concretely to the analytical continuum that associates escape, revolts and institutional transformations. Finally, we will try to objectify the specific stakes of mass evasion in relation to strict individual evasion.